2015
DOI: 10.5935/0103-5053.20150112
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Superficial Sediments of the Negro River in the Amazon Region of Brazil

Abstract: Polycyclic aromatic hydrocarbons (PAHs) were identified and quantified in samples of superficial sediments of the Negro River, in the Amazon region of Brazil, through analyses performed by GC/MS. Total PAH concentration that includes parent and alkylated PAHs ranged from 6.5 to 5348 ng g -1 of dry weight. The ∑16 PAHs prioritized in environmental studies by the U.S. Environmental Protection Agency (USEPA) ranged from 5.6 to 1187 ng g -1 . The most contaminated plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…The total parent PAH concentrations observed for the streams studied were also compared to those reported previously for sediments of the Negro river (AM), where ports, shipyards and petrol stations are located [6]. Most sediments from the Negro river presented total PAH concentrations similar to those found for the three streams of study [6].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The total parent PAH concentrations observed for the streams studied were also compared to those reported previously for sediments of the Negro river (AM), where ports, shipyards and petrol stations are located [6]. Most sediments from the Negro river presented total PAH concentrations similar to those found for the three streams of study [6].…”
Section: Discussionsupporting
confidence: 57%
“…The total parent PAH concentrations observed for the Amazonian streams were similar to those reported for other Brazilian areas, such as the Patos Lagoon (RS) (7.3-92.8 ng g −1 ) [39], the Sergipe river estuarine system (SE) (not detected-127.3 ng g −1 ) [40], the Amazon river estuary (AP) (22.2-158.9 ng g −1 ) [8], and the Capibaribe estuarine system (PE) (not detected-497.6) [41], but lower than those reported for areas of intense ship traffic, petroleum refinery, and intense urbanization and industrialization, such as the Itajaí-Açu estuarine system (SC) (28.4-1237.2 ng g −1 ) [10], the Cocó and Ceará rivers (CE) (3.04-2234.76 ng g −1 ) [42], and the Santos bay and estuary (SP) (60-8680 and 79.6-15389.1 ng g −1 ) [31,43]. The total parent PAH concentrations observed for the streams studied were also compared to those reported previously for sediments of the Negro river (AM), where ports, shipyards and petrol stations are located [6]. Most sediments from the Negro river presented total PAH concentrations similar to those found for the three streams of study [6].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Environmental contamination with PAHs has been reported by several researchers in Brazil revealing high concentrations of these compounds in river, dam, and estuary sediment (Brito et al 2005;Bícego et al 2006;Meire et al 2008;Leite et al 2011). Recently, a research study conducted with sediment samples from the Negro River in the Amazon showed that 70 % of the total abundance of priority PAHs were classified as high mo le cu lar w ei gh t, s uc h as c h rys en e, B aP, benzo(a)anthracene, and dibenzo(a,h)anthracene (Souza et al 2015).…”
Section: O T H E R G E N E R a O F B A S I D I O M Y C E T E S S U C mentioning
confidence: 99%
“…A contaminação e deposição de HPAs de alto peso molecular, tais como BaP, em sedimentos do rio Negro no estado do Amazonas, já vem sendo registrada na literatura (SOUZA et al, 2015). Desta forma, faz-se necessário medidas de mitigação do impacto ambiental causado por estes poluentes.…”
Section: Introductionunclassified